2016
DOI: 10.1016/j.earscirev.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Global synthesis of the classifications, distributions, benefits and issues of terracing

Abstract: For thousands of years, humans have created different types of terraces in different sloping conditions, meant to mitigate flood risks, reduce soil erosion and conserve water. These anthropogenic landscapes can be found in tropical and subtropical rainforests, deserts, and arid and semiarid mountains across the globe. Despite the long history, the roles of and the mechanisms by which terracing improves ecosystem services (ESs) remain poorly understood. Using literature synthesis and quantitative analysis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
152
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 241 publications
(159 citation statements)
references
References 118 publications
1
152
0
6
Order By: Relevance
“…Here, a greater drainage density resulted in accelerated runoff during storm rainfall, while an increased number of terrace levels along the hillslope diminished the surface gradient, thereby delaying response times and attenuating peak flows (Hallema and Moussa, 2014). These results are in line with observations in many other parts of the world (Di Lazzaro et al, 2015;Wei et al, 2016). For example, Kovář et al (2016) found similar effects of agricultural terraces on storm runoff on a similar-sized hillslope in Bohemia (Czech Republic); however, they used the kinematic wave approximation to route storm flow because of lower rainfall intensities and a possibly greater relative contribution from subsurface flow compared to Mediterranean and semi-arid watersheds.…”
Section: Wfiuh and The Evaluation Of Ecosystem Servicessupporting
confidence: 80%
“…Here, a greater drainage density resulted in accelerated runoff during storm rainfall, while an increased number of terrace levels along the hillslope diminished the surface gradient, thereby delaying response times and attenuating peak flows (Hallema and Moussa, 2014). These results are in line with observations in many other parts of the world (Di Lazzaro et al, 2015;Wei et al, 2016). For example, Kovář et al (2016) found similar effects of agricultural terraces on storm runoff on a similar-sized hillslope in Bohemia (Czech Republic); however, they used the kinematic wave approximation to route storm flow because of lower rainfall intensities and a possibly greater relative contribution from subsurface flow compared to Mediterranean and semi-arid watersheds.…”
Section: Wfiuh and The Evaluation Of Ecosystem Servicessupporting
confidence: 80%
“…The Loess Plateau, characterized by the deepest loess deposits in the world, not only has a unique landscape but is also known for its fragile ecosystem, which is especially vulnerable to soil erosion . Although some measures, such as the construction of check dams (Zhao, Mu, Wen, Wang, & Gao, 2013) and terraces (Wei et al, 2016), have resulted in prominent reductions in soil erosion, vegetation restoration has also had an important influence on soil and water conservation (Lu et al, 2012). In addition, vegetation plays a critical role in the global carbon cycle and provides important mechanisms in terrestrial ecosystems that enhance their carbon sequestration capacity and decrease greenhouse gas emissions (Bonan, 2008;Jackson et al, 2008;Pan et al, 2011;Piao et al, 2009).…”
mentioning
confidence: 99%
“…Land preparation techniques are the important methods for water conservation and ecosystem restoration along degraded slopes (S. L. Liu et al, ), particularly in the semiarid regions of the Loess Plateau (Chen et al, ; B. J. Fu et al, ). Specifically, land preparation techniques can recreate natural slopes and impede runoff during rainfall events by blocking potential water pathways (Diaz, Weatherhead, Knox, & Camacho, ), which can also result in changes to the soil conditions that may affect hydrological behavior (Wei et al, ). Studies revealed that the runoff coefficients of natural slopes are 2.79 to 11.50 times higher than those of slopes after land preparations (Darvishan, Homayounfar, & Sadeghi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Before plantations, terrace engineering and land preparation techniques were widely used across hillslopes to reduce soil erosion, improve water conservation, and accelerate vegetation restoration (Mcdonagh, Lu, & Semalulu, ; Wei et al, ). Generally, studies across the globe indicate that 60–96% reductions in runoff and sediment compared with that of natural slopes can be achieved by using diverse land preparation measures (J. G. Liu, Li, Ouyang, Tam, & Chen, ; J. Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%